An e-module development for vocational accounting students: Project-based learning media - Purnamasari, Niken; Sholekhah, Irmadatus; Guntoro, Dibyo Waskito (Wiyata Dharma: Jurnal Penelitian dan Evaluasi Pendidikan, 2025)
The limited adequate learning resources and productive subject teaching materials for vocational school students open up opportunities to develop teaching materials integrated with technology to master 21st-century skills. This research aims to develop e-modules based on Project-Based Learning to improve the skills of vocational school students. Development research is built with the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). This research is limited to the development stage at Wonosari Muhammadiyah Vocational School involving Class X Accounting Students. The e-module feasibility test was carried out by involving material experts, media experts, and student responses. Data collection was carried out through interviews, observations, and questionnaires. The feasibility of the e-module was analyzed using scores converted into four quantitative categories. The research output is in the form of an e-module softfile and guidelines for teachers and students. The e-module is also uploaded to the website to make it easier to access via a mobile web browser. The material validation test got an average score of 3.49 in the very decent category, while the media validation test got an average score of 3.58 in the very decent category. Furthermore, the student response results in the main field trial were 3.22, and the operational field trial was 3.33, getting the very feasible category. This e-module is appropriate for accounting learning to improve students' skills.